2017
DOI: 10.1371/journal.pntd.0005187
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Aedes aegypti JAK/STAT Pathway-Mediated Immunity to Dengue Virus

Abstract: We have developed genetically modified Ae. aegypti mosquitoes that activate the conserved antiviral JAK/STAT pathway in the fat body tissue, by overexpressing either the receptor Dome or the Janus kinase Hop by the blood feeding-induced vitellogenin (Vg) promoter. Transgene expression inhibits infection with several dengue virus (DENV) serotypes in the midgut as well as systemically and in the salivary glands. The impact of the transgenes Dome and Hop on mosquito longevity was minimal, but it resulted in a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
145
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(150 citation statements)
references
References 62 publications
1
145
1
3
Order By: Relevance
“…The specialization of the JAK/STAT pathway in mosquitoes was further revealed by a study that showed that the genetically modified strain of A. aegypti could regulate JAK/STAT components to DENV but not to ZIKV or chikungunya virus (CHIKV) infection (Jupatanakul et al . ; McFarlane et al . ).…”
Section: Functional Utilization Of Jak/stat Pathway In Insect Innatementioning
confidence: 99%
See 1 more Smart Citation
“…The specialization of the JAK/STAT pathway in mosquitoes was further revealed by a study that showed that the genetically modified strain of A. aegypti could regulate JAK/STAT components to DENV but not to ZIKV or chikungunya virus (CHIKV) infection (Jupatanakul et al . ; McFarlane et al . ).…”
Section: Functional Utilization Of Jak/stat Pathway In Insect Innatementioning
confidence: 99%
“…ND: No available data; Genbank accession numbers are represented in parenthesisRNAi-mediated downregulation of Cactus and PIAS, respectively. The specialization of the JAK/STAT pathway in mosquitoes was further revealed by a study that showed that the genetically modified strain of A. aegypti could regulate JAK/STAT components to DENV but not to ZIKV or chikungunya virus (CHIKV) infection(Jupatanakul et al 2017;McFarlane et al 2014). The JAK/STAT pathway core components under the ligands, receptor, kinases, and substrates category for A. aegypti have been shown inTable 4.…”
mentioning
confidence: 99%
“…It has also been reported that Aag-2 cells (a cell line of A. aegypti ) increase quantitatively with the expression of the STAT transcription factor during infections by SINV [66]. The activation of the JAK-STAT pathway does not favor per se resistance to ZIKV or CHIKV but does indeed do so in relation to DENV [89]. When combined with the Toll pathway, the JAK-STAT pathway enhances resistance to ZIKV in A. aegypti [90].…”
Section: The Immune Response In a Aegyptimentioning
confidence: 99%
“…However, this inhibition is far from complete. 40 RNA interference (RNAi) gene silencing is an important antiviral mechanism in Ae. aegypti.…”
Section: Artículo De Revisiónmentioning
confidence: 99%